The Integration of the Metaverse into Luxury Brand Marketing Strategies in South Korea : A Study of New Consumption Dynamics & Market Opportunities - Descoteaux, Michaël (2025)
This thesis aims to analyse the impact of the Metaverse on the luxury industry in South Korea. The main objective is to understand how luxury brands can integrate this emerging digital environment into their communication and promotional strategies with South Korean consumers. A qualitative survey, based on a series of interviews with around ten participants, enabled us to gather a wide range of perceptions. The results reveal a low level of enthusiasm for these virtual universes, as well as a marked lack of interest in the consumption of luxury products in this context. Several factors explain this reticence: a lack of understanding of how the Metaverse works, a lack of interest and difficulty in grasping the usefulness of luxury objects in the form of NFTs, and a certain distance from the world of luxury in general. These factors complicate the development of a coherent marketing strategy centred on the integration of these technologies. The conclusions of this study suggest that luxury brands would benefit from closely monitoring the development of the Metaverse adoption by South Korean consumers, while remaining cautious in order to avoid unprofitable investments or risks to their prestige image.